Adaptive problems arising out of the progenitor's abandonment after Zika Congenital Syndrome - Juliana Cristina Cruz Calazans; Paula Daniella de Abreu; Ednaldo Cavalcante de Araújo; Francisca Márcia Pereira Linhares; Cleide Maria Pontes; Ana Catarina Torres de Lacerda; Maria Gorete Lucena de Vasconcelos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to reveal the adaptive problems of the woman abandoned by the child's parent after Congenital Zika Syndrome, in the light of Roy's Adaptation Model. Method: a qualitative, descriptive study, based on Roy's Adaptation Model, developed with six women abandoned by their child's parent after Zika Congenital Syndrome diagnosis, through interview and Content Analysis technique. Results: adaptive problems appeared in nutrition, activity, rest, and protection patterns, due to limitations in self-care; self-concept, related to dissatisfaction with body image and personal being; in the role of transition role, through difficulties in taking over new roles and in interdependence, related to changes in affective needs. Final considerations: the overload of care for children with Congenital Zika Syndrome, added to the challenges of the abandoned woman by her child's parent, led to adaptive problems, showing their main difficulties of coping.